Competitividad de la industria manufacturera en México y Estados Unidos y su impacto en las relaciones comerciales 1990-2004 - Ayvar Campos, Francisco Javier (Universidad Michoacana de San Nicolás de Hidalgo, 2006)
he present research has as objective to know how the productivity determined the competitiveness of the manufacturer industry of Mexico and the United States during 1990-2004. Under this logic the industrial diagnose stands out that an enormous economic difference exists between both countries. Besides that in the case of our country an inverse relationship exists among the remunerations of the work and the added value that it generates while in United States that relationship is direct. On the other hand, you can also appreciate that it exists an economic, commercial and industrial relationship among these two countries expressed in terms of the flow of exports and imports, of the presence of transnational companies, and of the direct North American foreign investment in our country. When we obtain the indexes of revealed competitiveness, of total productivity of the factors and of partial productivity it is possible to observe that in general terms United States has a bigger revealed competitiveness in comparison to Mexico, however, deepening in the analysis we can notice that in durable goods our country has the advantage. Now with the purpose of understanding more in this respect we analyze the revealed competitiveness by divisions and it was possible to distinguish that our country has this advantage in the divisions I, VI and VIII and in some years in the divisions II, V and VII. However although that this competitiveness exists the level of total productivity and partial are smaller to those than it presents the American manufacturer industry. Therefore, the levels of competitiveness of the industry manufacturer and their divisions in comparison to United States are not explained totally by their level of productivity because they are smaller to those of United States, but also for the presence of other factors like the economic and commercial link among both industries and for the exchange rate, that reduces the value of the products manufactured in Mexico.

La tesis tiene como objetivo conocer en qué medida la productividad determinó la competitividad de la industria manufacturera de México y Estados Unidos durante el periodo 1990-2004. Bajo esta lógica se parte del diagnóstico industrial donde se destaca que existe una enorme diferencia en términos de personal ocupado, remuneraciones, formación bruta de capital, producto interno bruto, exportaciones e importaciones entre ambos países. Además de que en el caso de nuestro país existe una relación inversa entre las remuneraciones del trabajo y el valor agregado que genera mientras que en Estados Unidos dicha relación es directa. Por otro lado, se aprecia también que existe una estrecha relación económica, comercial e industria entre estos países expresada en términos del flujo de exportaciones e importaciones, de la presencia de empresas transnacionales y de la inversión extranjera directa norteamericana en nuestro país. Al obtener los índices de competitividad revelada, de productividad total de los factores y de productividad parcial se observa que en términos generales Estados Unidos tiene una competitividad revelada mayor a México, sin embargo, al profundizar en el análisis se puede advertir que en bienes duraderos nuestro país tiene la ventaja. Por lo tanto, nuestro país es más competitivo que Estados Unidos en ciertas dicciones, sin embargo, dicha competitividad no concuerda con los niveles de productividad de estas divisiones ya que son menores a los que presenta la industria manufacturera estadounidense. Es así como los niveles de competitividad de estas divisiones de la industria manufacturera en comparación a Estados Unidos no se explica totalmente por su nivel de productividad sino también por la presencia de otras factores como son el vínculo económico y comercial entre ambas industrias y por el tipo de cambio, que reduce el valor de los productos manufacturados en México.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias en Comercio Exterior
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2006-0007; Relaciones económicas; Sector manufacturero; Competitividad; Productividad; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/904